Commentary on: Kinley, J. L. and Reyno, S. M. “Dynamic Relational Group Psychotherapy: A Neurobiologically Informed Model of Change”. - Schermer, Victor L. (International Journal of Group Psychotherapy, 2016)
The author discusses research article “Dynamic Relational Group Psychotherapy: A Neurobiologically Informed Model of Change” published by J.L. Kinley and S.M. Reyno. He explores group psychotherapy’s development, and treatment considerations for brain along with interpersonal relations. He further compares Dynamic Relational Group Psychotherapy with other group development theories and shares the attachment trauma treatment, and identification of change agents in patients.